The role of the financial accounting system output in decision-making under IFRS standards - a study of economic institutions sample’s in Bechar state’s (2010-2019) - moumni, youcef; Bousmaha, mohamed (Journal of Research in Finance and Accounting, 2021)
The aim of this study is to clarify the contribution and role of the outputs of the financial accounting system in improving the decision-making process in economic institutions by first presenting the theoretical framework for the study related to the theoretical literature of the outputs of the financial accounting system and the standards for preparing financial reports and their various types, then dealing with the concept of the decision-making process and its various stages and classifications as well as the criteria controlling this process. While the descriptive approach made up the theoretical framework of the study, the field study consisted in surveying the opinions of a sample of professionals in the field of accounting, by using the questionnaire as a study tool, and analyzing the data collected using the SPSS V26 program, the study concluded that most economic institutions use the outputs of the financial accounting system as a primary source in order to improve the quality of the decision-making process.